A NEW RELATIONSHIP BETWEEN WAGES AND RENTS IN INDONESIA - Gidion P Adirinekso (Fakultas Bisnis UKDW, 2019)
This study examined the relationship between wages and house rents in the cities level. Merely, the existence of the housing market in the suburb is an critical component to explain relations between two market in two spaces. By applying practical and theoretical considerations, the house rents in suburb are included in this general equilibrium model. We utilize mathematical modeling to find some optimal equations in two markets to know the new relationship between wages and rents in the city level. An estimation using Non-Linear Seemingly Unrelated Regression to proof the relationship between wages and rents empirically. The work found that house rents in urban and suburban affecting wages in an urban area, it brings important policy implications in two markets. There are two considerations for the policy maker. They should consider others markets and spatial aspect when formulating their policies, especially in labor and housing markets Keywords: wages, house rents, urban labor economics. ABSTRAK Studi ini menguji hubungan antara upah dan sewa rumah di tingkat kota. Hanya saja, keberadaan pasar perumahan di pinggiran kota merupakan komponen penting untuk menjelaskan hubungan antara dua pasar dalam dua ruang. Dengan menerapkan pertimbangan praktis dan teoretis, sewa rumah di pinggiran kota dimasukkan dalam model keseimbangan umum ini. Kami menggunakan pemodelan matematika untuk menemukan beberapa persamaan optimal di dua pasar untuk mengetahui hubungan baru antara upah dan sewa di tingkat kota. Taksiran menggunakan Non-Linear Seemingly Unrelated Regression untuk membuktikan hubungan antara upah dan sewa secara empiris. Pekerjaan menemukan bahwa sewa rumah di perkotaan dan pinggiran kota mempengaruhi upah di daerah perkotaan, itu membawa implikasi kebijakan penting di dua pasar. Ada dua pertimbangan bagi pembuat kebijakan. Mereka harus mempertimbangkan pasar lain dan aspek spasial ketika merumuskan kebijakan mereka, terutama di pasar tenaga kerja dan perumahan. Kata kunci: upah, sewarumah, ekonomi tenaga kerja perkotaan JEL: C15, C33, C61, D50, J10, J20, R10